A scoping review of theories used to investigate clinician adherence to clinical practice guidelines - Derek Stewart (117849) (2022)
Background Routine utilization of evidence-based clinical practice guidelines (CPGs) is an effective strategy to optimize patient care and reduce practice variation. Healthcare professionals’ failure to adhere to CPGs introduces risks to both patients and the sustainability of healthcare systems. The integration of theory to investigate adherence provides greater insight into the often complex reasons for suboptimal behaviors. Aim To determine the coverage of literature surrounding the use of theory in studies of CPG adherence, report the key findings and identify the knowledge gaps. Method In April 2021, three bibliographic databases were searched for studies published since January 2010, adopting theory to investigate health professionals’ adherence to CPGs. Two reviewers independently screened the articles for eligibility and charted the data. A narrative approach to synthesis was employed. Results The review includes 12 articles. Studies were limited to primarily investigations of physicians, quantitative designs, single disease states and few countries. The use of behavioral theories facilitated pooling of data of barriers and facilitators of adherence. The domains and constructs of a number of the reported theories are captured within the Theoretical Domains Framework (TDF); the most common barriers aligned with the TDF domain of environmental context and resources, fewer studies reported facilitators. Conclusion There is emerging use of behavioral theories investigating physicians’ adherence to CPGs. Although limited in number, these studies present specific insight into common barriers and facilitators, thus providing valuable evidence for refining existing and future implementation strategies. Similar investigations of other health professionals are warranted. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-022-01490-9